Advancing Human Skin Equivalents: The Crucial Role of Neurovascular Integration - Hao Wu; Lorenzo Moroni; Nicolas Lebonvallet; Vincent Flacher; Paul Wieringa (Advanced Healthcare Materials, 2026)
ABSTRACT The integration of vascular and peripheral nerve components into bioengineered human skin equivalents (HSEs) represents a major advancement in regenerative medicine and biomedical research. While research has established vascularized HSE models, the role of neurovascular interactions in skin physiology and pathophysiology remains underexplored, particularly in translational or clinical contexts. These interactions are crucial for sensory perception, nutrient transport, thermoregulation, and immune modulation, making the development of vascularized and innervated HSE an important goal. Here, we first describe the anatomical and physiological roles of the vascular and peripheral nerve systems in the skin, focusing on their intricate relationships and significance to illnesses. This review then highlights recent advancements in engineering vascular and nerve structures in HSE, including strategies such as transwell‐based systems, 3D bioprinting, and organ‐on‐chip models. Despite significant progress, challenges remain in establishing functional neurovascular networks, achieving long‐term stability, and ensuring reproducibility. By addressing these challenges, neurovascularized HSE can enhance our understanding of skin physiology and pathology while advancing applications in disease modeling, drug testing, wound healing, and personalized medicine.